Interactive robogami: An end-to-end system for design of robots with ground locomotion. (September 2017) - Schulz, Adriana; Sung, Cynthia; Spielberg, Andrew; Zhao, Wei; Cheng, Robin; Grinspun, Eitan; Rus, Daniela; Matusik, Wojciech
This paper aims to democratize the design and fabrication of robots, enabling people of all skill levels to make robots without needing expert domain knowledge. Existing work in computational design and rapid fabrication has explored this question of customization for physical objects but so far has not been able to conquer the complexity of robot designs. We have developed Interactive Robogami, a tool for composition-based design of ground robots that can be fabricated as flat sheets and then folded into 3D structures. This rapid prototyping process enables users to create lightweight, affordable, and materially versatile robots with short turnaround time. Using Interactive Robogami, designers can compose new robot designs from a database of print-and-fold parts. The designs are tested for the users' functional specifications via simulation and fabricated on user satisfaction. We present six robots designed and fabricated using a 3D printing based approach, as well as a larger robot cut from sheet metal. We have also conducted a user study that demonstrates that our tool is intuitive for novice designers and expressive enough to create a wide variety of ground robot designs.